Perceived Difference in Typefaces to The Desirability of Products - KUANG, LEI (2019)
The main topic of this dissertation paper is semiotics, namely the study of signs. In this field, a large number of researchers have taken notice of the importance of typography, especially font styles in communicating connotative meanings. This paper seeks to determine the perceived differences in typefaces, especially those between serif type styles and sans serif groups at first. It then focuses on the effective response to the desirability of products. Font-product congruity has been tested to figure out whether it would have an impact on product choices. The paper would turn to find what factors, namely of which people’s demographic or psychographic patterns, would have a role to play on customers’ acceptance of the products that dressed in a serif typeface. As for the methodology, this paper adopts an overall quantitative method to be congruent with most of the works that are rooted in the typographic researches. According to a review of the literature on perceptions of logotype, a digital questionnaire was designed to collect relevant data for solving the research questions. Overall, a number of 215 people participated in this research of which is a repeated-measures and full-factorial design. In addition, for the design of the questionnaire, descriptors that belongs to either Evaluation (E), Potency (P) or Activity (A) dimension proposed by Osgood et al. (1957) were selected to test the connotative meanings behind fonts. Analysis of the response shows that there is a significant difference between a serif typeface and a sans-serif style in both Evaluation (E) dimension pointed out by Osgood et al. (1957) and Luxury (L) dimension identified by the author. Then, the results also reveal that the perception of a classic logotype of a strong brand in Activity (A) dimension can predict one’s purchase intention to the products that dressed in a simple bold sans-serif typeface. When it comes to factors that would act as predictors in raising people’s purchase intention of the products that are decorated by a simple heavy logotype, it can draw to the conclusion that individual differences in concerning price or in financial constraints would increase the desirability. Based on these results, it can come to a conclusion that people can perceive different affective meanings from fonts and their perceptions would be influenced by a serif factor. In addition, the results also indicate that individual differences would change people’s desirability of products. Further research should be carried out to explore the underlying reasons for the phenomenon.